Effects of aerobic exercise on metabolic indicators and physical performance in adult NAFLD patients: A systematic review and network meta-analysis. Issue 14 (7th April 2023) - Liu, Yangjun; Xie, Wei; Li, Juan; Ossowski, Zbigniew
Abstract : Background: nonalcoholic fatty liver disease (NAFLD) is characterized by excessive accumulation of fat in the liver without alcoholism. We conducted a systematic review and meta-analysis to elucidate the efficacy of aerobic exercise on metabolic indicators and physical performance of adult patients with NAFLD. Methods: To conduct the systematic review and network meta-analysis, 2 researchers searched PubMed, EBSCO, and Web of science databases to identify randomized clinical trials of aerobic exercise interventions for adults with NAFLD published between inception and July 2022. We assessed the methodological quality of the included literature using the Cochrane Risk Assessment Scale and the PEDro Scale. Relevant data were extracted, variables were converted to the same units, and meta-analysis was performed using RevMan 5.4 software. We compared mean differences (MD) between experimental and control groups. For each outcome analyzed, we expressed data as MD with 95% CI to compare metabolic markers and exercise capacity between the experimental and control NAFLD patients. Results: Eleven randomized clinical trials with a total of 491 individuals with NAFLD were included in accordance with the criteria of this study. Types of aerobic exercise include moderate or high-intensity interval running, cycling, Nordic walking, equipment training, etc; Training duration 4 to 16 weeks, 30 to 60 minutes 3 or more times a week. Compared with the control group, aerobic exercise group had reduced weight of patients, (MD) 1.20 kg (95% CI: −1.38 to −1.01 kg, P < .00001). Seven studies confirmed that aerobic exercise significantly reduced triglycerides, (MD) 3.00 mg/dL (95% CI: −5.80 to −0.21 mg/dL, P = .04); increased high density lipoproteins (MD) 5.96 mg/dL (95% CI: 2.95 to 8.96 mg/dL, P = .0001) and reduced low-density lipoproteins (MD) 6.45 mg/dL (95% CI: −8.53 to −4.37 mg/dL, P < .00001); the study also showed that aerobic exercise reduced the liver enzymes aspartate aminotransferase and alanine aminotransferase to varying degrees. Aerobic exercise can improve physical performance and increase peak oxygen consumption of (MD) 6.29 mL/Kg*minutes, (95% CI: 3.05–9.53mL/Kg*minutes, P = .0001). Conclusion: Aerobic exercise significantly reduced weight and improved metabolic index and physical performance. Impacted by the limitations of various regimens, doses, duration, center settings, populations enrolled, the study had certain limitations. The randomized controlled trials with larger sample sizes, multiple centers, and high quality should be conducted to validate the above conclusion. Further studies will be required to focus on the total duration of the intervention, duration and frequency of sessions, and intensity that are optimal for the promotion of physical performance and metabolic capacity in this population.